(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Customer satisfaction isthe key for company’s boom and sustainability of today’s competitive marketingworld. A company ought to know their customers’ sense towards products andservices. The study enables firms to scrutinize the changes in customersatisfaction, so that company can act swiftly to satisfy them. Appraisal ofcustomer satisfaction for unrelenting perfection is a prerequisite for anycompany. Customer retention is also money-spinning; companies will amplifyprofits by having better customer loyalty and satisfaction. Customers who arediscontented tell twice as many people about it as compared to contented ones.The Indian cellphone manufacturing companies like Videocon, Onida are havingconvincingly good products and also they are priced comparatively less withforeign players. The market statistics in India indicate that foreign companiesBlackberry, Htc, have achieved greater heights. The Indian key players Onidaand Videocon are not able to get a bigger pie. The study aims to analyze thesatisfaction level of customers towards cellphone products of LG, Onida &Videocon. The sample size of 300 respondents is taken from three major citieslike Karnal, panipat and Yamuna nagar. Thus it is analyzed with statisticaltools like standard deviation, arithmetic mean and testing hypothesis withchi-square test.